ANALYTICAL AND SYNTHETIC ACCOUNTING OF PAYROLL IN BUDGETARY ORGANIZATIONS - Klara Abdullayevna Yusupova (Modern American Journals, 2026)
This article examines analytical and synthetic accounting of payroll in budgetary organizations, focusing on how the two accounting layers jointly ensure completeness, traceability, and control of labor-cost recognition. Payroll is treated as a high-materiality expenditure item that affects budget execution, financial reporting credibility, and compliance with labor and public-finance rules. The study clarifies the functional division between synthetic accounting, which aggregates payroll-related liabilities and expenses by general ledger accounts, and analytical accounting, which disaggregates payroll data by employees, accrual types, funding sources, cost centers, and periods. The article emphasizes that effective payroll accounting in budgetary entities must reconcile three logics at once: the economic substance of compensation, the legal framework of employment relations, and the constraints of budget classifications and appropriations. Attention is paid to typical process stages, including timekeeping, payroll calculation, tax and social contribution withholding, payment execution, and subsequent reconciliation. The research outlines key control points that reduce risks of over-accruals, duplicate payments, incorrect classifications, and weak documentation, with special emphasis on segregation of duties, automated validation rules, and periodic matching between analytical registers and general ledger balances. The paper also highlights the role of standardized primary documents, internal regulations, and integrated information systems in improving data quality and shortening closing cycles. The findings argue that payroll accounting quality is less dependent on the mere presence of software and more on consistent chart-of-This article examines analytical and synthetic accounting of payroll in budgetary organizations, focusing on how the two accounting layers jointly ensure completeness, traceability, and control of labor-cost recognition. Payroll is treated as a high-materiality expenditure item that affects budget execution, financial reporting credibility, and compliance with labor and public-finance rules. The study clarifies the functional division between synthetic accounting, which aggregates payroll-related liabilities and expenses by general ledger accounts, and analytical accounting, which disaggregates payroll data by employees, accrual types, funding sources, cost centers, and periods. The article emphasizes that effective payroll accounting in budgetary entities must reconcile three logics at once: the economic substance of compensation, the legal framework of employment relations, and the constraints of budget classifications and appropriations. Attention is paid to typical process stages, including timekeeping, payroll calculation, tax and social contribution withholding, payment execution, and subsequent reconciliation. The research outlines key control points that reduce risks of over-accruals, duplicate payments, incorrect classifications, and weak documentation, with special emphasis on segregation of duties, automated validation rules, and periodic matching between analytical registers and general ledger balances. The paper also highlights the role of standardized primary documents, internal regulations, and integrated information systems in improving data quality and shortening closing cycles. The findings argue that payroll accounting quality is less dependent on the mere presence of software and more on consistent chart-of-
Keywords: Payroll accounting, analytical accounting, synthetic accounting, budgetary organizations, public sector accounting, general ledger, payroll accruals, compensation expenses, wage liabilities, deductions and withholdings, internal control, budget classification, cost centers, funding sources, reconciliation, audit trail, financial reporting, compliance, month-end closing, information systems.